Pengaruh Latihan Sirkuit Training Terhadap Gerakan Handspring Untuk Atlet Junior Senam Artistik Di Kota Semarang (Indonesian Journal for Physical Education and Sport, 2020)
Abstract The background of this research is the need of handspring movement training methods for junior artistic gymnastics athletes in Semarang. Writer found a problem that is junior artistic gymnastics athletes in Semarang lacking mastery of floor handspring movement. The purpose of this research is to improve the technique and physical ability of junior artistic gymnastics athletes in Semarang in order to master the handspring movement properly and correctly.This is an experimental research, using Matching Subject Desaign. The steps used are: (1) initial test (pre test) (2) group division (3) treatment (4) final test (postest) (5) data analysis. The results of this study were obtained from the results of the t-test it can be seen that the practice pattern 1 t count 2.54012163 and t table (0.05) (6) = 2.44691 (df = 6). Therefore t arithmetic 2.54012163> t table 2.44691 and the value of these results indicate there are significant differences. From the results of the t-test it can be seen that the practice of pattern 2 t count 1.921608 and t (0.05) (5) = 2.57058 (df = 5). Therefore t count 1.921608 <t table 2.57058 and the value of these results indicate that there are less significant differences. The conclusion obtained from the data is that circuit training pattern 1 has more significant influence than circuit training pattern 2 for the handspring movements of junior artistic gymnastics athletes in Semarang. Advice for junior artistic gymnastic in Semarang is to use circuit training pattern 1 for practice the handspring movement.